Univerzitetne knjižnice v Albaniji - Ifti, Margarita (Organizacija znanja, 2006)
Contemporary Albania inherited a government-managed higher education system, which eventually collapsed. Universities are emerging and developing in an unregulated environment with insufficient financial support The libraries, though still very "modest", are the ones that have achieved the highest level of organisation. They, however, are still at the beginning of exploring the possibilities of linking with each other. Universities are endeavouring to join COBISS.Net and introduce the COBISS library information system. This would enable the national research information system E-CRIS.AL to be set up, and make research much more transparent.
Keywords: Albania; Albanija; bibliotekarstvo; bolonjski proces; library science; visokošolske knjižnice